PD0325901, an ERK inhibitor, enhances the efficacy of PD-1 inhibitor in non-small cell lung carcinoma - Min Luo; Yuhui Xia; Fang Wang; Hong Zhang; Danting Su; Chaoyue Su; Chuan Yang; Shaocong Wu; Sainan An; Suxia Lin; Liwu Fu (Elsevier, 2021)
ERK pathway regulated the programmed death ligand-1 (PD-L1) expression which was linked to the response of programmed death-1 (PD-1)/PD-L1 blockade therapy. So it is deducible that ERK inhibitor could enhance the efficacy of PD-1 inhibitor in cancer immunotherapy. In this study, PD0325901, an oral potent ERK inhibitor, strongly enhanced the efficacy of PD-1 antibody in vitro and in vivo models in non-small cell lung carcinoma (NSCLC) cells. Mechanistically, PD0325901 or shRNA-ERK1/2 significantly downregulated the PD-L1 expression in NSCLC cells and increased the CD3+ T cells infiltration and functions in tumor tissue. There was a positive correlation between the p-ERK1/2 expression and PD-L1 expression in patients with NSCLC. And the patients with low p-ERK1/2 expression were observed a high response rate of PD-1/PD-L1 blockage therapy. Our results demonstrate that PD0325901, an ERK inhibitor, can enhance the efficacy of PD-1 blockage against NSCLC in vitro and in vivo models. And the combination of ERK inhibitor such as PD0325901 and PD-1/PD-L1 blockage is a promising regimen and encouraged to be further confirmed in the treatment of patients with NSCLC.